(untitled) - Ishikawa, Shigeru (Tokyo, 1967)
This volume, constituting the eighth in the Economic research series (in English) of the Hitotsubashi institute of economic research, brings out studies of professor Shigeru Ishikawa on economic development, with the purpose of clarifying some of the basic facts and problems of the contemporary developing economies and exploring the real policy alternatives among which these economies must choose
Keywords: Economic policy,Chính sách kinh tế; Japan,Nhật Bản